1995
DOI: 10.2307/2937157
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal Dynamics of the Bivalve Gemma Gemma in a Patchy Environment

Abstract: The purpose of this study was to analyze the dispersal dynamics of the ovoviviparous bivalve Gemma gemma (hereafter referred to as Gemma) in an environment disturbed by the pit—digging activities of horseshoe crabs, Limulus polyphemus. Gemma broods its young and has no planktonic larval stage, so all dispersal is the result of juvenile and adult movement. Animal movement was measured using natural crab pits, hand—dug simulated crab pits, and cylindrical bottom traps in the intertidal zone at Tom's Cove, Virgin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
72
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(77 citation statements)
references
References 76 publications
4
72
1
Order By: Relevance
“…Although Mya arenaria and Gemma gemma have been found in the water column in some studies (M. arenaria, Möller 1986;G. gemma, Sellmer 1967), our data and other studies (Emerson & Grant 1991, Commito et al 1995a, Hunt & Mullineaux 2002 suggest that if sediment transport at a site can be predicted, the likelihood of transport of juvenile M. arenaria, and other bivalves whose dispersal is generally linked to sediment transport, also can be predicted. It is likely that some dispersal of juvenile M. arenaria and G. gemma does occur at low flow speeds when individuals do not burrow into the sediment.…”
Section: Relationship Between Clam Transport and Sediment Erosionmentioning
confidence: 81%
See 1 more Smart Citation
“…Although Mya arenaria and Gemma gemma have been found in the water column in some studies (M. arenaria, Möller 1986;G. gemma, Sellmer 1967), our data and other studies (Emerson & Grant 1991, Commito et al 1995a, Hunt & Mullineaux 2002 suggest that if sediment transport at a site can be predicted, the likelihood of transport of juvenile M. arenaria, and other bivalves whose dispersal is generally linked to sediment transport, also can be predicted. It is likely that some dispersal of juvenile M. arenaria and G. gemma does occur at low flow speeds when individuals do not burrow into the sediment.…”
Section: Relationship Between Clam Transport and Sediment Erosionmentioning
confidence: 81%
“…Less information was available for G. gemma than for M. arenaria, and no relationship was detected between the weight of sediment and the proportion of G. gemma transported at Sites 1 and 3, possibly due to the smaller range of sediment erosion. Previous field studies on M. arenaria (Emerson & Grant 1991) and G. gemma (Commito et al 1995a) found positive relationships between the number of clams and the amount of sediment collected in bedload traps. At the shear velocities employed in this study, clams and sand grains rolled along the bottom as bedload and were collected in the trap.…”
Section: Relationship Between Clam Transport and Sediment Erosionmentioning
confidence: 99%
“…Results of previous studies suggest that dispersal of Gemma gemma and Mya arenaria, which were expected to be common in the Navesink estuary, is generally linked to bedload transport (Emerson & Grant 1991, Commito et al 1995a, Hunt & Mullineaux 2002. Cylindrical traps were installed flush with the sediment surface to measure the flux of clams and sediment transported as bedload or falling out of suspension in the water column.…”
Section: Methodsmentioning
confidence: 99%
“…Emerson & Grant 1991, Commito et al 1995a,b, Turner et al 1997, Hunt & Mullineaux 2002, Lundquist et al 2006). On intertidal flats, there are positive relationships between wind conditions and flux of sediment and bivalves in sediment traps (Emerson & Grant 1991, Commito et al 1995b, Armonies 1996, Turner et al 1997.…”
Section: Introductionmentioning
confidence: 99%
“…There are few studies of infaunal population dynamics over extended spatial scales in relation to benthoscape structure, and it is not clear whether the populations form metapopulations and can be studied within a metapopulation framework. Benthic ecologists are beginning to understand processes that link populations by transport of larvae and/or adults (e.g., Dobbs and Vozarik 1983;Committo et al 1995;Bradbury and Snelgrove 2001). Larval mixing and the degree to which populations interact via larval transport can differ depending on the type of coastal environment (Keough and Black 1996).…”
Section: Discussionmentioning
confidence: 99%